An Evaluation of Inoculant Additives on Cell Viability and Their Effects on the Growth and Physiology of Glycine max L. - Francisco Rafael Santos da Conceição; Layara Alexandre Bessa; Marconi Batista Teixeira; Bárbara Gonçalves Cruvinel; Luciana Cristina Vitorino (Agronomy)
The development of efficient bioinoculant formulations requires compounds with stabilizing, thickening, and carrier functions to preserve microbial viability and promote biological activity in soil. However, the majority of studies evaluate inoculant formulations predominantly in terms of bacterial viability, overlooking other important performance parameters. This study employed an integrative approach combining in vitro and plant-based assays to assess the effects of starch, carboxymethyl cellulose (CMC), and trehalose in formulations containing Azospirillum brasilense, Bradyrhizobium diazoefficiens, Methylobacterium symbioticum, and Paenibacillus alvei, applied to Glycine max seeds. Our hypothesis was that the presence of these additives, each with distinct functional roles (starch as a slow-release carbon source, CMC as a structural agent and protector against physical stress, and trehalose as an osmoprotectant and membrane stabilizer), would influence not only bacterial viability but also the seed germination, growth, and physiological responses of inoculated G. max plants. Starch improved viability in A. brasilense formulations, while both starch and trehalose had positive effects on M. symbioticum. These additives also enhanced plant traits, including dry biomass, chlorophyll content, carboxylation efficiency (A/Ci), and photochemical efficiency (Fv/Fm and Pi_Abs). Trehalose was particularly effective in formulations with B. diazoefficiens and M. symbioticum, supporting its use as a versatile stabilizer. In contrast, CMC (0.25%) negatively impacted bacterial viability, especially for B. diazoefficiens and P. alvei, and impaired physiological parameters in G. max when combined with M. symbioticum. These results highlight the need to evaluate formulation components not only for their physical roles but also for their specific interactions with microbial strains and effects on host plants. Such an integrative approach is essential for designing stable, efficient bioinoculants that align with sustainable agricultural practices.